Learner’s Mental Model and the need for the Creative Teacher - MEGA, Afaf (University of Eloued جامعة الوادي, 2016)
This paper endeavors to shed light on the learner’s mental model, its importance in understanding the learner’s mental representation regarding his learning experience. Sometimes, the wrong mental model might lead to wrong interpretations and wrong future decisions which might hinder the learning situation as a whole. Therefore, the presence of the creative teacher to deal with the learner’s mental model is crucial as he inquires and seeks for alternatives to solve the learning problems. On the light of this, our paper is divided into two main parts; in the first, we will discuss the importance of knowing learner’s mental model for both the teacher and the learner and the role of the creative teacher in dealing with it. Whereas in the second part, which will be practical, we will test second year students’ mental models regarding oral expression class using one of the measuring tools to come up in the end with some results and recommendations
THE SECOND NATIONAL CONFERENCE ON LANGUAGE, MIND AND LEARNER'S COGNITIVE CAPACITIES March, 7th/8th 2016 University of Eloued
Keywords: Learner’s, Mental Model, the need for the Creative Teacher.